Preaching water but drinking wine? Relative performance evaluation in international banking - Dragan Ilić; Sonja Pisarov; Peter S. Schmidt (University of Zurich, Department of Economics, 2015)
Relative performance evaluation (RPE) is, at least on paper, enjoying widespread popularity in determining the level of executive compensation. Yet existing empirical evidence of RPE is decidedly mixed. Two principal explanations are held responsible for this discord. A constructional challenge arises from intricacies of identifying the correct peers. And on a simpler note, corporate commitments to RPE could be mere exercises in empty rhetoric. We address both issues and test the use of RPE in a new sample of large international non-U.S. banks. Taken as a whole, the banks in our sample show moderate evidence consistent with RPE. We report stronger evidence once we investigate the subsample of banks that disclose the use of peers in their compensation schemes. This finding lends support to the credibility and thus informational value of RPE commitments. Digging deeper, we conclude that RPE usage is driven by firm size and growth options.
Keywords: J33; D86; G3; G21; 330; Relative Performance Evaluation; Executive Compensation; Peers; Banks; Disclosure